Implementasi Keselamatan Dan Kesehatan Kerja (K3) Pada Kantor Pusat PT X - Nanda Iswara; Nadia Amanah (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The occurrence of work accidents is of course not expected by everyone because in addition to harming themselves it can also harm the company, the need for regulations governing safety and health at work, with the regulations expected office workers will be safe and comfortable in carrying out their work. The regulations that have been issued should indeed be implemented by workers. The purpose of this study is to determine the implementation of OHS at the Head Office of Company X and to find out the efforts of Company X in preventing potential work accidents. The research method used is descriptive qualitative method by collecting data through observation and analysis of documents related to OHS Office. The results showed that the implementation of OSH at company X was in accordance with the standards of Permenkes RI Number 48 of 2016 as evidenced by the existence of fire extinguishers, evacuation route instructions and the use of work tools such as tables and chairs that were appropriate. The efforts of the company's head office in preventing work accidents by applying the zero accident principle are expected to reduce the number of work accidents.